Susceptibility of carbapenem-resistant Enterobacterales isolates to new antibiotics from a tertiary care hospital, Egypt: A matter of hope - Shahenda G Badran; Mai M Malek; Rehab M Ateya; Amira H Afifi; Mahmoud M Magdy; Eman S Elgharabawy (Journal of Infection in Developing Countries)
Introduction: Carbapenem-resistant Enterobacterales (CRE) are particularly worrisome pathogens because of their resistance to last-resort antibiotics, significant morbidity, and mortality. With limited treatment options, new therapeutic choices have become available for the management of CRE infections. Data regarding the efficacy of these novel agents are still limited particularly in a low-middle-income country like Egypt. This study aims to assess the prevalence of different carbapenemase genes among CRE isolates and the susceptibility of these isolates to novel antibiotics for improving antibiotic policy and infection control strategies in Egypt.